931 Occupational skin cancer in outdoor workers in italy: expected number vs cases recognised by the italian national compensation authority (inail). (24th April 2018) - Modenese, Alberto; Korpinen, Leena; Gobba, Fabriziomaria
Abstract : Introduction: Solar Ultraviolet Radiation (UV) is one of the main risk factors for Non Melanoma Skin Cancer (NMSC) and Malignant Melanoma (MM). In Italy, only considering agriculture, fishery and construction sectors, the approximate number of workers exposed to solar UV (Outdoor workers –OW-) is 2 million (1.6 million males, 4 00 000 females). Our aim is to compare the number of skin cancers (SCs) expected in OW to the number recognised by the Italian National Compensation Authority (INAIL). Methods: We collected data of Italian National Cancer Registres and the INAIL database of occupational diseases, including cancer, respectively available on the websites www.registri-tumori.it and www.bancadaticsa.inail.it Results: In Italy the yearly incidence of MM is 14, 2 per 1 00 000 in males and 13 per 1 00 000 in females, that of NMSC 119.4 per 1 00 000 in males and 90.7 per 1 00 000 in females. Applying these incidence rates to the Italian OW number, the expected SCs per year are approximately 2561 (279 MMs and 2282 NMSCs). INAIL recognised as occupational disease n. 246 cases (20% MM vs 80% NMSCs) in the last 5 years, i.e. less than 50 cases per year. Discussion and conclusions: Our results show that, in Italy, the National Compensation Authority recognises less than the 2% of the cases expected to occur in OW each year: 50 vs 2500. Main limitations of these data are that the incidence rates applied to OWs were not standardised, that the number of solar UV related SCs calculated is possibly under-estimated, considering that, e.g., not all OW groups were included, and that the data from cancer registries were quite outdated while the SCs incidence is increasing. In conclusion, our data suggest a large under-estimation of occupational SCs in Italy, and that a better recognition of these diseases in OW is a relevant, and urgent, problem.